The translation of policy to person: a qualitative analysis of elite athletes' perceptions of pregnancy in the United Kingdom - Caro, C. V.; Trow, S.; Bell, Z.; Flynn, A. C.; Lavelle, F. (Sports Medicine, 2025)
Background: An increasing number of female athletes are navigating an athletic career alongside pregnancy. Limited qualitative research has investigated the experiences of elite athletes in the United Kingdom (UK). This study aimed to explore the experiences of elite athletes in the UK as they navigated pregnancy, employing a socio-ecological framework to inform future research and policy recommendations on sport participation during pregnancy. Methods: A descriptive qualitative study design, adopting a relativist ontology and constructivist epistemology, was implemented. Semi-structured online interviews were conducted with elite athletes = 18 years old, who resided in the UK, and who trained and/or competed at the highest level of their sport prior to and/or during pregnancy. Interviews were recorded, transcribed and analysed using reflexive thematic analysis. Results: Eleven athletes (mean age 31 ± 3 years) from nine team and individual sports participated in the study. Four key themes were developed: (1) From the Podium to Parenthood: Institutional versus Individual Influence on Reproductive Planning; (2) Is My Career Over? Micro Level Support versus Macro Level Doubt and Worry; (3) Athlete to Mother: Internal Conflict to Community Role Model; (4) Navigating the Bump: Individual Drive to Tackle Systemic Gaps. Conclusions: Findings highlight the complexity female athletes face when navigating pregnancy, motherhood and elite sport. There is a need for high-quality research focusing on preconception and pregnancy-specific training and nutrition modifications for elite athletes, particularly regarding nutrient intake and supplementation. Additionally, efforts to improve the translation of evidence-based research into practical applications remain essential.